Distribution and characteristics of Pleistocene ground thermal contraction polygons in Europe from satellite images. (18th January 2022) - Bertran, Pascal
Abstract: The study of Pleistocene polygons in Europe carried out using the collection of satellite images available in Google Earth™ provides new data on the distribution of ground cracking by thermal contraction during glacial periods and sheds light on some factors controlling their formation. The distribution map shows that thermal contraction cracking affected terrain between latitude 43.5°N and the southern limit of the Fennoscandian Ice Sheet at 15 ka, with a concentration of polygons north of latitude 51°N. A clear asymmetry exists in relation to longitude, with a greater southward extension of polygons in France (43.5°N) than in central Europe (47°N). Analysis of the characteristics of polygons at the European scale reveals an association with lithology, latitude, and the age of the sediments in which they formed. The morphological evolution over time reconstructed from observations of polygons of contrasting ages indicates that a stable mature phase, characterized by small (mean size 15 m), regular polygons with numerous Y‐junctions, is reached after ca. 4 ka of thermal contraction cracking activity.